CSR and perceived price fairness : an analysis on willingness to pay and perceived benefit - Eusébio, Eduardo Marques (2020)
The objective of this study is to assess the potential effect that engagement in Corporate Social Responsibility (CSR) may have on consumers’ Perceived Price Fairness. Following the literature that already developed on this topic, the study approaches the knowledge gap in the field by, simultaneously, considering Willingness to Pay, here measured using the Price Sensitivity Meter by Van Westendorp (1976) and Perceived Benefit of active CSR engagement. The study followed an experimental approach via an online survey, concerning three types of products and two social causes supported by CSR engagement. To gather insights, the study follows the Price Sensitivity Meter framework to measure different pricing options and strategies for products from firms who actively engage in CSR. The results point put that to two of the three products under analysis make for increased Willingness to Pay. On all cases, respondents pointed out an increase in added perceived benefit when faced with CSR activities. On the two cases where a positive effect was registered, consumers’ Perceived Benefit increase outmeasured the growth in Willingness to Pay, making a case that CSR engagement indeed provides for an increase in Perceived Price Fairness. In one of the cases. Consumers recognized an increase on Perceived Benefit but their Willingness to Pay followed an opposite direction.